EVALUATION OF COMBINED EFFECTS OF THERMAL AND MECHANICAL STRESSES ON THE PRESSURE VESSEL - Swati S. Kumbar; Prof. G.R. Deshpande (International Journal of Innovations in Engineering Research and Technology, 2023)
One of the several plant components for which stress evaluations must be done is the pressure vessel. Primary stresses and secondary stresses are the two basic types of stresses that a pressure vessel endures. Pressure within the pressure vessel causes primary strains, while heat loading causes secondary stresses. An enormous amount of thermal stress occurs in a pressure vessel that handles hot fluid. Typically, thermo-mechanical loadings are present in liquid metal reactors (LMR). Induced stresses are determined analytically using pressure vessel ASME codes or theory. In this study, coupled field analysis for thermo-mechanical loading with ANSYS is used to compute induced stresses. The outcomes are next contrasted with analytical outcomes. The use of a commercial FEA tool instead of an analytical technique is demonstrated in this study. Thermal stress may be calculated using empirical connections provided by analytical solutions like ASME and Japanese Code. In the pressure vessel industry, using FEA tools is not particularly common. This type of loading necessitates coupled field analysis for FEA. In this study, coupled field analysis is carried out using ANSYS.